Performance analysis of smart grid dynamic HAN over Rician fading channel. Issue 2 (14th October 2020) - Padhan, Ashish Kumar; Sahu, P. R.; Samantaray, S. R.
Abstract : In smart grid (SG) communications, the home area network (HAN) plays a vital role in managing data transmission among communicating devices through a smart meter (SM). Rician fading distribution closely replicates an indoor communication channel in SG HAN system. Thus, channel link is modeled as a Rician fading channel in this paper and Multi‐user selection scheme is employed in SM. Further, a closed‐form expression for average bit error probability (ABEP) performance of indoor dynamic HANs with communicating devices using phase‐shift keying (PSK) modulation is derived and analyzed the effect of traffic intensity, the total number of devices and Rician factor for the considered system. The expression for average channel capacity (ACC) of the SG HAN system is also derived and analyzed by varying the parameters of interest.